The Role of Radiologic Technology in Enforcing Diagnosis of Covid-19 Disease: Case Report at RSPAW Salatiga - Lilik Lestari (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2020)
Coronavirus has become a world pandemic since WHO announced it in March 2020. This study aims to report on the role of radiologic technology in helping to diagnose the Covid-19 disease handled by RSPAW Salatiga. The research method chosen was descriptive-analytic case reports. The results of the study explained that radiologic technology of chest X-Ray was able to provide an image of Covid-19 with 89% sensitivity, namely the discovery of reticulonodular, ground-glass opacity (GGO), crazy paving, consolidation, location in the periphery of the lung, and the inferior lobe of the lung.